The Spatiotemporal Evolution of MRI-Derived Oxygen Extraction Fraction and Perfusion in Ischemic Stroke - Wu, Di; Zhou, Yiran; Cho, Junghun; Shen, Nanxi; Li, Shihui; Qin, Yuanyuan; Zhang, Guiling; Yan, Su; Xie, Yan; Zhang, Shun; Zhu, Wenzhen; Wang, Yi (Frontiers in Neuroscience, 2021)
Purpose: To access the spatiotemporal evolution of oxygen extraction fraction (OEF) in ischemic stroke by a newly developed cluster analysis of time evolution (CAT) for a combined quantitative susceptibility mapping and quantitative blood oxygen level-dependent model (QSM + qBOLD, QQ). Method: One hundred and fifteen patients in different ischemic stroke phases were retrospectively collected for measurement of OEF of the infarcted area defined on diffusion-weighted imaging. Clinical severity was assessed by National Institutes of Health Stroke Scale (NIHSS). Of the 115 patients, 11 underwent two longitudinal MRI scans including 3D mGRE and 3D pCASL to evaluate the reversal region (RR) of the initial diffusion lesion (IDL) that did not overlap with the final infarct (FI). The temporal evolution of OEF and cerebral blood flow (CBF) in the IDL, the RR and the FI was assessed. Results: Compared to the contralateral mirror area, OEF of the infarcted region was decreased regardless of stroke phases (p < 0.05) and showed a declining tendency from acute to chronic phase (p = 0.022). Five of the 11 patients with longitudinal scans showed reversal of the IDL. Relative OEF (rOEF, compared to the contralateral mirror area) of the RR increased from first to second MRI (p = 0.044). CBF was about 1.5-fold higher in the IDL than the contralateral mirror area in the first MRI. Two patients showed penumbra according to enlarged FI volume. The rOEF of the penumbra fluctuated around 1.0 at earlier scan times and then decreased while CBF decreased continuously. Conclusions: The spatiotemporal evolution of OEF and perfusion in ischemic lesions is heterogeneous and the CAT-based QQ method is feasible to capture cerebral oxygen metabolic information.